A calibrated gravity model of interregional trade. Issue 1 (2nd January 2023) - Cai, Mattia
ABSTRACT: Lack of interregional trade data is often a major obstacle when doing economic analysis at the subnational level. This paper discusses a calibration procedure for estimating bilateral trade between the regions of a country. Our approach can be equivalently characterized as an application of the gravity-RAS or the doubly constrained gravity model method. Either way, a crucial element is represented by the distance elasticity parameter, which the user is expected to provide exogenously. We propose a way of estimating that parameter using standard econometric methods with readily available data and demonstrate our calibration procedure in a case study of Italy.